2020
DOI: 10.1186/s12883-020-01996-7
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease: current assessment methods and wearable devices for evaluation of movement disorder motor symptoms - a patient and healthcare professional perspective

Abstract: Background Parkinson’s disease is the second most common long-term chronic, progressive, neurodegenerative disease, affecting more than 10 million people worldwide. There has been a rising interest in wearable devices for evaluation of movement disorder diseases such as Parkinson’s disease due to the limitations in current clinic assessment methods such as Unified Parkinson’s Disease Rating Scale (UPDRS) and the Hoehn and Yahr (HY) scale. However, there are only a few commercial wearable device… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 61 publications
0
48
1
Order By: Relevance
“…Furthermore, disease severity and progression are characterized using the Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS), which is also based on observation of clinical features associated with PD [3,4]. These types of assessments are subjective and prone to overlooking small changes in motor function that are representative of the disease, which poses challenges for PD screening [5]. This makes additional clinical tools that can be layered on to clinical evaluations by neurologists all the more critical [6].…”
Section: Introduction 1parkinson's Disease Symptoms and Standard Diagnosis Methodsmentioning
confidence: 99%
“…Furthermore, disease severity and progression are characterized using the Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS), which is also based on observation of clinical features associated with PD [3,4]. These types of assessments are subjective and prone to overlooking small changes in motor function that are representative of the disease, which poses challenges for PD screening [5]. This makes additional clinical tools that can be layered on to clinical evaluations by neurologists all the more critical [6].…”
Section: Introduction 1parkinson's Disease Symptoms and Standard Diagnosis Methodsmentioning
confidence: 99%
“…Our results are in line with these findings and demonstrate that in PD, the connectome-based identifiability conveys the severity of the disease. Since the UPDRS is one of the most reliable and used motor scales in the clinical settings [33][34][35] , we believe that a scalar score, based on the whole connectome conveying subject-specific features of the brain functional connectivity may be of help in the management of the disease.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Then, we obtained the time series of 116 regions of interest (ROIs), based on the AAL atlas 45 , using the volume conduction model proposed by Nolte 46 , and applying the Linearly Constrained Minimum Variance 47 beamformer algorithm included in the Fieldtrip toolbox 42 . The resulting time series were band-pass filtered in each canonical frequency band (i.e., delta (0.5 -4 Hz), theta (4 -8 Hz), alpha (8 -13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)). Only 90 ROIs were selected for further analysis, since we excluded ROIs related to the cerebellum because of low reliability.…”
Section: Source Reconstructionmentioning
confidence: 99%
“…Due to issues of cognitive limitations and other risk factors associated with aging, studies have suggested that elderly users, especially PWDs exhibit resistance to the use of healthcare devices [ 2 , 13 ]. Notwithstanding the existence of these studies, other research and projects have demonstrated that, with the right approach to design considerations, this resistance could be reduced tremendously, leading to the adoption of wearable devices by PWDs [ 14 , 15 , 16 , 17 , 18 , 19 ]. For instance, studies have revealed that GPS-based wireless tracking devices, such as GPS Smart Sole, Freedom GPS Locator Watch, Safe-link, Mindme Locate, MXLOCareTM, iTraq3, and PocketFinder+, and others, such as Fitbit, Mi band, Oura ring, and Alice PDx, have been preferred and widely used by PWDs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%